Internal living environment and respiratory disease in children: findings from the Growing Up in New Zealand longitudinal child cohort study. Issue 1 (December 2016) - Tin Tin, Sandar; Woodward, Alistair; Saraf, Rajneeta; Berry, Sarah; Atatoa Carr, Polly; Morton, Susan; Grant, Cameron
Abstract Background The incidence of early childhood acute respiratory infections (ARIs) has been associated with aspects of the indoor environment. In recent years, public awareness about some of these environmental issues has increased, including new laws and subsequent changes in occupant behaviours. This New Zealand study investigated current exposures to specific risk factors in the home during the first five years of life and provided updated evidence on the links between the home environment and childhood ARI hospitalisation. Methods Pregnant women (n = 6822) were recruited in 2009 and 2010, and their 6853 children created a child cohort that was representative of New Zealand births from 2007-10. Longitudinal data were collected through face-to-face interviews and linkage to routinely collected national datasets. Incidence rates with Poisson distribution confidence intervals were computed and Cox regression modelling for repeated events was performed. Results Living in a rented dwelling (48%), household crowding (22%) or dampness (20%); and, in the child's room, heavy condensation (20%) or mould or mildew on walls or ceilings (13%) were prevalent. In 14% of the households, the mother smoked cigarettes and in 30%, other household members smoked. Electric heaters were commonly used, followed by wood, flued gas and unflued portable gas heaters. The incidence of ARI hospitalisation before age five years was 33/1000 person-years. The risk of ARI hospitalisation was higher for children living in households where there was a gas heater in the child's bedroom: hazard ratio for flued gas heater 1.69 (95% CI: 1.21-2.36); and for unflued gas heater 1.68 (95% CI: 1.12-2.53); and where a gas heater was the sole type of household heating (hazard ratio: 1.64 (95% CI: 1.29-2.09)). The risk was reduced in households that used electric heaters (Hazard ratio: 0.74 (95% CI: 0.61-0.89)) or wood burners (hazard ratio: 0.79 (95% CI: 0.66-0.93)) as a form of household heating. The associations with other risk factors were not significant. Conclusions The risk of early childhood ARI hospitalisation is increased by gas heater usage, specifically in the child's bedroom. Use of non-gas forms of heating may reduce the risk of early childhood ARI hospitalisation.